PEMBELAJARAN MENULIS TEKS NEGOSIASI DENGAN MENGGUNAKAN METODE PROBLEM BASED LEARNING PADA SISWA KELAS X TAHUN AJARAN 2017/2018 - Peryoga Trisna Pamungkas; Nur Mufidah Fauziyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This writing aims to describe the implementation of Problem Based Learning method in learning to write negotiation text so that students can solve the problem of describing the result of learning writing negotiation text by using Problem Based Learning method and describe difficulty difficulties in learning writing negotiation text. This research uses quasi experimental method with pre-experimental design design. The test technique is in the form of writing negotiation text and nontest technique in the form of observation. The result of the research at pretest stage obtained the average value of 62,39 whereas after got treatment by using method of Problem Based Learning (postest) got the average value 80,18 based on that obtained that problem based learning method can be used for learning writing negotiation text in senior high school